Metabolic patterns and biotransformation activities of resveratrol in human glioblastoma cells: relevance with therapeutic efficacies. - Xiao-Hong Shu; Hong Li; Xiao-Xin Sun; Qian Wang; Zheng Sun; Mo-Li Wu; Xiao-Yan Chen; Chong Li; Qing-You Kong; Jia Liu (PLoS ONE, 2011)
BACKGROUND: Trans-resveratrol rather than its biotransformed monosulfate metabolite exerts anti-medulloblastoma effects by suppressing STAT3 activation. Nevertheless, its effects on human glioblastoma cells are variable due to certain unknown reason(s). METHODOLOGY/PRINCIPAL FINDINGS: Citing resveratrol-sensitive UW228-3 medulloblastoma cell line and primarily cultured rat brain cells/PBCs as controls, the effect of resveratrol on LN-18 human glioblastoma cells and its relevance with metabolic pattern(s), brain-associated sulfotransferase/SULT expression and the statuses of STAT3 signaling and protein inhibitor of activated STAT3 (PIAS3) were elucidated by multiple experimental approaches. Meanwhile, the expression patterns of three SULTs (SULT1A1, 1C2 and 4A1) in human glioblastoma tumors were profiled immunohistochemically. The results revealed that 100 µM resveratrol-treated LN-18 generated the same metabolites as UW228-3 cells, while additional metabolite in molecular weight of 403.0992 in negative ion mode was found in PBCs. Neither growth arrest nor apoptosis was found in resveratrol-treated LN-18 and PBC cells. Upon resveratrol treatment, the levels of SULT1A1, 1C2 and 4A1 expression in LN-18 cells were more up-regulated than that expressed in UW228-3 cells and close to the levels in PBCs. Immunohistochemical staining showed that 42.0%, 27.1% and 19.6% of 149 glioblastoma cases produced similar SULT1A1, 1C2 and 4A1 levels as that of tumor-surrounding tissues. Unlike the situation in UW228-3 cells, STAT3 signaling remained activated and its protein inhibitor PIAS3 was restricted in the cytosol of resveratrol-treated LN-18 cells. No nuclear translocation of STAT3 and PIAS3 was observed in resveratrol-treated PBCs. Treatment with STAT3 chemical inhibitor, AG490, committed majority of LN-18 and UW228-3 cells but not PBCs to apoptosis within 48 hours. CONCLUSIONS/SIGNIFICANCE: LN-18 glioblastoma cells are insensitive to resveratrol due to the more inducible brain-associated SULT expression, insufficiency of resveratrol to suppress activated STAT3 signaling and the lack of PIAS3 nuclear translocation. The findings from PBCs suggest that an effective anticancer dose of resveratrol exerts little side effect on normal brain cells.